Fabrication of b-oriented titanium silicalite films on silicon wafer under stepwise steam assisted crystallisation. (November 2013) - Zhuang, Z.; Jiang, X.; Peng, D. Y.; Lv, W. J.; Xin, F.
Abstract : A stepwise steam assisted crystallisation (SAC) method was developed for directly growing a highly b -oriented titanium silicalite (TS-1) film on silicon wafer. The influences of crystallisation methods and the volume ratios of water on TS-1 films were investigated. The XRD patterns showed that the highly b -oriented TS-1 film could be fabricated with the ratio of 5·2 at 413 K for 24 h and 448 K for 36 h. Interestingly, the FESEM images revealed that the morphologies of the films changed greatly with the volume ratios of water in autoclave to that on silicon wafer. The crystals aggregately grew while the ratio was 2·6. Whereas, the crystals grew cuboid with the ratio of 5·2, and finally to regular prismatic shape while the ratios were 10·4 and 15·6. This facile stepwise SAC method could provide a potential strategy to prepare oriented molecular sieve films.